Polycentric Governance in Investment Management in West Sulawesi Province - Amujib, ‎; Ibrahim, Akmal (KnE Social Sciences, 2025)
The regional government of West Sulawesi Province continues to strive to encourage increased investment. However, in its implementation, it faces various challenges in polycentric governance. Therefore, this study aims to describe investment management and analyze polycentric governance in investment management in West Sulawesi Province. The research approach used is qualitative. Observations were made on various investment governance activities. Research interviews were conducted with informants involved and contributing to investment governance. Research documentation includes statistical and supporting data on investment. Data analysis consists of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results indicate that the management of investment was not implemented effectively. Based on the polycentric governance approach, it shows that: First, coordination between institutions in the West Sulawesi Provincial Government has been carried out in a structured and collaborative manner with various parties, namely across regional apparatus organizations and vertical institutions. Second, distribution of authority in investment management in West Sulawesi is carried out with a clear distribution of roles and responsibilities between the provincial government, districts/cities, and related institutions. It is not effective, but it can be improved by improving coordination between institutions, increasing resource capacity, and ensuring that policies implemented are aligned at all levels of government. If this is done, investment management in the region will be more efficient and have a positive impact on economic growth.